Iranian EFL Teachers’ Perceptions of Burnout Sources: A Qualitative Study - Seyedeh Maryam Mousavi; Ali Amirghassemi; Mahnaz Saeidi (Journal of English Language Pedagogy and Practice, 2022)
This qualitative study aims to investigate the sources of burnout from Iranian EFL teachers’ perspectives. To this end, thirty-four Iranian male and female EFL teachers participated in the semi-structured interview to comment on the burnout sources and then rank them in terms of priority. Also, one hundred teachers responded to an online open-ended questionnaire. The coding scheme revealed two external and internal nodes, five themes, and fifteen subthemes. Under the external node lay financial, organizational, and teacher training problems. The internal node involved teachers’ psycho-affective traits and personal life affairs. The results showed that external sources outweighed the internal ones. Among the external sources, teachers’ low pay, the supervisor’s maltreatment, and workload, and among the internal ones, teachers’ low problem-solving abilities, low motivation and self-efficacy held high ranks. No one attributed burnout to teachers’ gender and age, and almost all participants unanimously criticized the educational administration system of Iran for not providing teachers with the necessary means of burnout recognition and prevention. The study has implications for educational policymakers and practitioners.